Conexão com a natureza e bem-estar subjetivo indicado por felicidade em idosos - (:unkn) unknown (Universidade Federal do Amazonas)
The aging process brings either a biological, psychological, and social changes of a person. The term Connection with Nature (CN) is used in Psychology as a subjective bond of vital interaction with the natural world.CN has been identified as a predictor of happiness, or subjective well-being (BES) of people and that people who feel connected to nature want to protect it and have motivations to adopt ecological behaviors. To study elderly population is to accept that this group of people actively participates in life in cities because of improvements in health conditions and consequent increase in life expectancy. This study deals with the elderly population that resides in the Amazona and that had an intense contact with nature in the past. Therefore, studying the elderly-environment relationship is justifiable. The objective of the study was to verify the CN levels among the elderly in the metropolitan region of Manaus AM (Manaus, Iranduba, Manacapuru and Careiro da Castanho, Novo Airão) and if the different NC levels influence the BES, here indicated as levels of subjective happiness. A semi-structured interview was used whose protocol contained open and closed questions and a CN and EFS scale. Participants were 62 elderlies between 60 and 83 years of age (Fem=23; M=36). The responses were audio-recorded and after being transcribed, they were inserted into an Excel and SPSS spreadsheet for analysis. The results show that most elderly people have high levels of CN as well as subjective happiness. However, these psychological constructs are not associated, so that CN is not a predictor of subjective happiness manifested by the elderly. In this sense, the perception of happiness may have other elements that are acting to make it feel that way, and that CN levels do not necessarily imply happiness for these participants. CN and FES as psychic states are not mutually associated for these elderly people. It was also found that the elderly who consider nature as part of their identity are the same ones who say they feel close to nature in their current home, even living in urban areas. The item on the CN scale with the lowest relative average was the interest in spending vacations in remote and isolated places. This item for the elderly in this study with low income and past experiences in the Amazon, seems to be unbalancing the general average of CN, which leads to infer that this item must be revised when considering the population of elderly Brazilians. However, it was found that the elderly who declared themselves to be less happy are also the ones who are least concerned with environmental problems. This result is significant in the sense that unhappiness acts directly on the lack of care for the environment, thus, the subjective happiness of the elderly does not seem to influence the type of concern with environmental problems.

The aging process brings either a biological, psychological, and social changes of a person. The term Connection with Nature (CN) is used in Psychology as a subjective bond of vital interaction with the natural world.CN has been identified as a predictor of happiness, or subjective well-being (BES) of people and that people who feel connected to nature want to protect it and have motivations to adopt ecological behaviors. To study elderly population is to accept that this group of people actively participates in life in cities because of improvements in health conditions and consequent increase in life expectancy. This study deals with the elderly population that resides in the Amazona and that had an intense contact with nature in the past. Therefore, studying the elderly-environment relationship is justifiable. The objective of the study was to verify the CN levels among the elderly in the metropolitan region of Manaus AM (Manaus, Iranduba, Manacapuru and Careiro da Castanho, Novo Airão) and if the different NC levels influence the BES, here indicated as levels of subjective happiness. A semi-structured interview was used whose protocol contained open and closed questions and a CN and EFS scale. Participants were 62 elderlies between 60 and 83 years of age (Fem=23; M=36). The responses were audio-recorded and after being transcribed, they were inserted into an Excel and SPSS spreadsheet for analysis. The results show that most elderly people have high levels of CN as well as subjective happiness. However, these psychological constructs are not associated, so that CN is not a predictor of subjective happiness manifested by the elderly. In this sense, the perception of happiness may have other elements that are acting to make it feel that way, and that CN levels do not necessarily imply happiness for these participants. CN and FES as psychic states are not mutually associated for these elderly people. It was also found that the elderly who consider nature as part of their identity are the same ones who say they feel close to nature in their current home, even living in urban areas. The item on the CN scale with the lowest relative average was the interest in spending vacations in remote and isolated places. This item for the elderly in this study with low income and past experiences in the Amazon, seems to be unbalancing the general average of CN, which leads to infer that this item must be revised when considering the population of elderly Brazilians. However, it was found that the elderly who declared themselves to be less happy are also the ones who are least concerned with environmental problems. This result is significant in the sense that unhappiness acts directly on the lack of care for the environment, thus, the subjective happiness of the elderly does not seem to influence the type of concern with environmental problems.
Keywords: Bem-estar social; Envelhecimento - Aspectos sociais; Qualidade de vida; CIENCIAS HUMANAS; Idoso; Bem-estar subjetivo; Conexão com a Natureza; Felicidade. Amazônia